Novel tricyclic diamines 2. Synthesis of 1, 7-diazaisoadamantane, 1, 5-diazaisoadamantane and 1, 6-diazahomobrendane. Issue 8 (21st February 2018) - McDonald, Ivar M.; Mate, Robert; Ng, Alicia; Park, Hyunsoo; Olson, Richard E.
Graphical abstract: Highlights: Novel diazaisoadamantane and diazahomobrendane tricycles were prepared. Synthesis relies on saturation of aromatic azaindole followed by intramolecular cyclization. Requisite azaindole intermediates accessed convienently from the halo aminopyridines. Structures of novel tricycles confirmed by X-ray crystallography. Abstract: Three novel tricyclic diamines (1, 7-diazaisoadamantane, 1, 5-diazaisoadamantane and 1, 6-diazahomobrendane) were prepared. A flexible synthetic strategy was employed which used flat, aromatic azaindoles as the starting materials. The requisite azaindoles were prepared by a tandem Sonogashira coupling/intramolecular cyclization reaction. Ring saturation, appropriate functionalization and intramolecular alkylation provided the three novel tricyclic diamines cores.